The Influence of Brand Image, Brand Trust, and Lifestyle on Purchasing Decisions of Azarine Sunscreen Products in Mojokerto - Fiska Rahma Hismawan; Sugeng Purwanto (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to examine the influence of brand image, brand trust, and lifestyle on consumers’ purchase decisions of Azarine Sunscreen products in Mojokerto. A recent overclaim controversy surrounding Azarine raised public concerns about the accuracy of product information, prompting the need to reassess consumer perceptions and decision-making processes. Using a quantitative approach, data were collected from 96 respondents through an online Likert-scale questionnaire and analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS. The study reveals that brand image, brand trust, and lifestyle all have positive effects on purchase decisions. The findings emphasize the importance of cultivating a trustworthy and emotionally resonant brand while aligning marketing strategies with consumers’ lifestyles to foster long-term brand engagement in the skincare industry.